Research review on coaches' perceptions regarding the teaching strategies experienced in coach education programs - Ciampolini, V.; Milistetd, M.; Rynne, S. B.; Zeilmann Brasil, V.; Vieira do Nascimento, J. (International Journal of Sports Science & Coaching, 2019)
Using a learner-centered perspective underpinned by a constructivist view of learning, the aim of this research was to analyze the scientific articles published from 2009 to 2016 concerning sports coaches' perceptions on the teaching strategies experienced in coach education programs. The search for articles took place across six databases: PUBMED, SCOPUS, Web of Science, PyscNET, ERIC, and SPORTDiscus. Two peer-reviewed journals related to sports coaching that were not indexed in the aforementioned databases at the time of the review were also screened. A total of 1937 articles were initially found with 17 eventually deemed appropriate for incorporation into the review after applying the established exclusion criteria. Three themes related to interactive, reflective, and assessment activities were generated from an inductive thematic analysis conducted on the coaches' quotes extracted from the reviewed articles. In general, it was revealed that coaches mostly held positive perceptions of situations and experiences that positioned them at the center of the learning process through interaction and reflection. Suggestions are discussed to address coaches' negative perceptions on the assessment strategies experienced and to improve the integration of learner-centered approaches in coach education initiatives.